Effect of Oral Sacchromycesboulardii Treatment Against Experimental Infection with Enterotoxigenic E.coli in Mice - Saleh, Shahlaa M; Ahmed, Manhal F; Hadi, Sabreen A (Al-Nahrain Journal of Science, 2018)
This study was designed to evaluate histological changes in intestine of mice treated with Sacchromycesboulardii and infected with enterotoxigenic Escherichia coli (ETEC). Twenty albino male mice were divided into four groups, and designated 1, 2, 3, and 4. Each group consisted of 5 mice and subjected to the followings treatments; Group1; used as a negative control.Group2; was infected with enterotoxigenic E.coli culture and use as positive control. Group3; was dosed with S.boulardii; Group4; was dosed with S.boulardii culture, and infected with ETEC E.coli. Histopathological study showed that infection of mice with ETEC causes a necrosis, degenerative changes and inflammatory cells infiltration in intestinal sections as compared with normal section taken from uninfected mice, while dosing with S.boulardii prevented the cytotoxic effect of ETEC in mice.